Surgical infarct volume reduction and functional outcomes in patients with ischemic cerebellar stroke: results from a multicentric retrospective study - Hernandez Duran, Silvia; Walter, Johannes; Dubinski, Daniel; Freiman, Thomas Michael; Naser, Paul; Unterberg, Andreas; Won, Sae-Yeon; Geßler, Florian (Journal of neurosurgery, 2024)
OBJECTIVE Recent work on ischemic cerebellar stroke has suggested that the resection of infarcted tissue may lead to improved functional outcomes compared with decompressive surgery alone. Nonetheless, no studies have assessed the extent to which necrotic tissue should be resected or if there are any volumetric thresholds capable of predicting functional outcomes in this patient population. In this study, the authors aimed to determine potential thresholds for volume reduction in ischemic cerebellar stroke in an effort to optimize the management of ischemic cerebellar stroke and, in so doing, improve functional outcomes. METHODS This study is a multicentric retrospective study of patients who underwent surgery for the management of ischemic cerebellar stroke. Volumetric analyses of infarcted tissue present on CT scans were performed before and after surgical intervention(s). The final infarct volume (FIV) was computed as a percentage of the initial infarct volume (postoperative infarct volume/preoperative infarct volume × 100). The primary endpoint was functional outcome at 3 months, as determined by the modified Rankin Scale (mRS) score; mRS scores 0-2 were considered as favorable and mRS scores 3-6 as unfavorable. Receiver operating characteristic curves were used to explore the relationship between postoperative infarct volumes and FIV versus mRS score, and Youden’s index was used to estimate potential volumetric thresholds. RESULTS A total of 91 patients were included in the study. The mean pre- and postoperative infarct volumes were 45.25 (SD 18.32) cm3 and 29.56 (SD 26.61) cm3, respectively. Patients undergoing necrosectomy, regardless of whether via craniotomy or craniectomy, were more likely to have a favorable outcome at discharge (OR 16.62, 95% CI 2.12-130.33; p = 0.008) and at 3 months (OR 24.12, 95% CI 3.03-192.18; p = 0.003) postoperatively. Postoperative infarct volumes ≤ 17 cm3 yielded a sensitivity of 77% and a specificity of 68% with regard to the prediction of favorable outcome at 3 months. The resection ≥ 50% of infarcted tissue was also predictive of favorable outcomes at 3 months (OR 7.7, 95% CI 2.7-21.8; p < 0.001). CONCLUSIONS The reduction of necrotic tissue volumes by at least 50% and/or the reduction of the infarct volume by ≤ 17 cm3 appear to be associated with favorable outcomes in patients with surgically managed ischemic cerebellar strokes.